Contribution of Resistivity Properties in Estimating Hydraulic Conductivity in Ciremai Volcanic Deposits - Deden Zaenudin Mutaqin; Hendarmawan Hendarmawan; Agus Didit Haryanto; Undang Mardiana; Febriwan Mohammad (Universitas Negeri Gorontalo, 2023)
The hydraulic parameters of porous media, such as porosity (φ) and hydraulic conductivity (K), are the most important factors for planning and managing water exploitation from aquifers. This study aims to estimate the hydraulic conductivity parameters using the geoelectric method on volcanic deposits on the northern slope of Mount Ciremai. For this purpose, four data types were used to estimate K and φ, including lithological profiles, water table, groundwater quality, pumping test data, and vertical electrical sounding (VES). Based on Archie's law and Kozeny's equation, we get the alpha (α) values and cementation factor (m) from which the median values of α = 1.01 and m = 1.36 represent the studied aquifer. The porosity (φ) of the aquifer varies from 0.097 to 0.187 with an average of 0.141 and is spatially related to the hydraulic conductivity (kgm), which varies from 4.97 × 10-6 to 6.75 × 10-5 m/s after the application of Kozeny's equation. The hydraulic conductivity (Kp) calculated from the pumping tests varies from 9.07 × 10-6 to 1.06 × 10-4 m/s and is strongly correlated (r = 0.87). Furthermore, a relation between resistivity and hydraulic conductivity was established for the studied aquifer to estimate these parameters in sites lacking data.